(untitled) (Journal of Social Sciences Review, 2025)
This research explores the intersection of sustainability and social evils, particularly focusing on the role of equitable governance in mitigating climate change. It argues that social injustices, such as poverty, inequality, and discrimination, exacerbate environmental degradation and hinder effective climate action. The study aims to analyze how inequitable governance structures contribute to these challenges and propose equitable governance models that integrate social justice and environmental sustainability. Using a qualitative research design, the study reviews case studies, including the Green New Deal, the Paris Agreement, and indigenous knowledge systems, to illustrate the potential for inclusive, just governance in addressing both climate change and social evils. The findings emphasize the need for participatory decision-making, transparency, and fairness in policy formulation to ensure that marginalized communities have a voice in climate action. The research further emphasizes that to endure climate change mitigation measures, it is necessary to dismantle structural inequalities and take up governing models that are equitable. It leads to governance frameworks that bring together environmental protection with social justice, thus building a more just and industrially advanced global civil society towards lasting climate resilience.